2021
DOI: 10.1016/j.respe.2021.07.006
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID-19 epidemic on primary care in South-eastern France: implementation of a real-time monitoring system based on regional health insurance system data

Abstract: Résumé Position du problème L’épidémie de Covid-19 du printemps 2020 a fortement affecté le système de soins. Le confinement et les risques d'exposition au coronavirus ont incité les patients à modifier leur recours aux soins. L'objectif était de partager un retour d'expérience sur la mise en place d'un dispositif de surveillance en temps réel de l'activité des médecins libéraux de la région Provence-Alpes-Côte d'Azur, et de l’évolution des remboursements de médicaments prescrits aux … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…The prevalence of insomnia symptoms was 23.2%. The symptom was higher in young adults than adolescents, and higher in adolescents than in children (18%, 25.3% and 25.7% insomnia in children, adolescents and young adults respectively) (Davin-Casalena et al, 2021).…”
Section: Prevalence Of Mental Health Illnessesmentioning
confidence: 86%
“…The prevalence of insomnia symptoms was 23.2%. The symptom was higher in young adults than adolescents, and higher in adolescents than in children (18%, 25.3% and 25.7% insomnia in children, adolescents and young adults respectively) (Davin-Casalena et al, 2021).…”
Section: Prevalence Of Mental Health Illnessesmentioning
confidence: 86%
“…During the pandemic and compared to the previous year, the proportion of patients with medications increased in our study and for SGLT-2 and GLP-1 a significant effect was attributable to the pandemic. Other studies observed: an increase in insulin [ 39 ] and both insulin and OAD medications [ 40 , 41 ], during the first month of pandemic as compared to the year before; a decrease in OAD during the first four months of the pandemic [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reduction in follow-up visits in type 2 diabetes patients was independent of age, sex, and educational level [ 20 ]. Other studies investigated the reasons to avoid or postponed the visit during lockdown [ 3 , 40 ]. Differently from [ 20 ], we found that dropout of youngest patients, age ≤ 40 years, was the most affected by the pandemic, PAF 37%(30, 43)% though the oldest ones, age > 80 years, had the highest risk of dropout, after correcting for confounders.…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare use has been challenged during the COVID-19 pandemic ( 1 ), particularly during the first epidemic wave and the first lockdown, which lasted from 17 March to 10 May 2020 in France ( 2 , 3 ). Two subsequent lockdowns, although less restrictive than the first one, were implemented in France to contain the second epidemic wave- from 30 October to 15 December- and the third one – from 3 April to 2 May 2021.…”
Section: Introductionmentioning
confidence: 99%